Sociotechnical Systems View of Catalysts that Enable Underrepresented Minority Student Success. (September 2022) - Pennathur, Priyadarshini; Quiroz, Brissa; Bisantz, Ann; Everett, Louis; Pennathur, Arunkumar
Academic institutions in the US have recently refocused their attention on Diversity, Equity, and Inclusion. This panel consisting of engineering faculty, administrators and industry professionals will discuss how colleges of engineering can approach the problem of recruiting, retaining, and graduating undergraduate underrepresented minority (URM) students by using a sociotechnical systems modeling approach. The main thrust of the discussion is how an academic organizational system such as a college of engineering can be broken down into a social system consisting of the people (students, faculty, staff and other stakeholders), and a technical system consisting of programs and initiatives for URM student success. Joint analyses of the social system and the technical system can then reveal systemwide barriers and opportunities for enabling URM student success.